Podoconiosis, trachomatous trichiasis and cataract in northern Ethiopia: A comparative cross sectional study - Burn, Helen (PLoS Negl Trop Dis, 2017)
BACKGROUND: Rural populations in low-income countries commonly suffer from the co-morbidity of neglected tropical diseases (NTDs). Podoconiosis, trachomatous trichiasis (both NTDs) and cataract are common causes of morbidity among subsistence farmers in the highlands of northern Ethiopia. We explored whether podoconiosis was associated with cataract or trachomatous trichiasis (TT) among this population. METHODS: A comparative cross-sectional study was conducted in East Gojam region, Amhara, Ethiopia in May 2016. Data were collected from patients previously identified as having podoconiosis and from matched healthy neighbourhood controls. Information on socio-demographic factors, clinical factors and past medical history were collected by an interview-administered questionnaire. Clinical examination involved grading of podoconiosis by examination of both legs, measurement of visual acuity, direct ophthalmoscopy of dilated pupils to grade cataract, and eyelid and corneal examination to grade trachoma. Multiple logistic regression was conducted to estimate independent association and correlates of podoconiosis, TT and cataract. FINDINGS: A total of 700 participants were included in this study; 350 podoconiosis patients and 350 healthy neighbourhood controls. The prevalence of TT was higher among podoconiosis patients than controls (65 (18.6%) vs 43 (12.3%)) with an adjusted odds ratio OR 1.57 (95% CI 1.02–2.40), p = 0.04. There was no significant difference in prevalence of cataract between the two populations with an adjusted OR 0.83 (95% CI 0.55–1.25), p = 0.36. Mean best visual acuity was 0.59 (SD 0.06) in podoconiosis cases compared to 0.44 (SD 0.04) in controls, p<0.001. The proportion of patients classified as blind was higher in podoconiosis cases compared with healthy controls; 5.6% vs 2.0%; adjusted OR 2.63 (1.08–6.39), P = 0.03. CONCLUSIONS: Individuals with podoconiosis have a higher burden of TT and worse visual acuity than their matched healthy neighbourhood controls. Further research into the environmental and biological reasons for this co-morbidity is required. A shared approach to managing these two NTDs within the same population could be beneficial.